Exploratory Factor Analysis (EFA) on Principals' Instructional Leadership Practices, Teacher Commitment, and Student Engagement - Khalid, Khalina; Ibrahim, Abdullah (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2025)
The principal who implements instructional leadership practices has been shown to enhance teachers' commitment to their careers, which subsequently serves as a catalyst for student achievement, providing key indicators of excellence in education. This article aims to validate the instruments measuring Instructional Leadership, Teacher Commitment, and Student Achievement using Exploratory Factor Analysis (EFA). The instructional leadership instrument comprises 20 items, the teacher commitment instrument consists of 18 items, and the student achievement instrument contains 22 items. The study employs a quantitative analysis, with data collected through questionnaires. The sampling method utilized includes stratified random sampling and simple random sampling. A total of 374 respondents, all teachers from daily secondary schools in the state of Kedah, Darul Aman, Malaysia, participated in the study. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) Version 27.0. The results of the EFA analysis revealed that the instructional leadership variable is represented by 20 items (no items were excluded), teacher commitment is represented by 18 items (no items were excluded), and student achievement is represented by 22 items (no items were excluded). Overall, the EFA results demonstrate that these instruments are appropriate for the primary research within the context of daily secondary school teachers in Kedah, Darul Aman. Additionally, the article provides evidence-based statistical guidelines for conducting EFA to ensure the validity of research instruments, ensuring their relevance to the specific context of the study.